Isolation and characterization of five novel probiotic strains from Korean infant and children faeces - Kook, Sun-Young (PLoS One, 2019)
Probiotics are dietary supplements containing viable, non-pathogenic microorganisms that interact with the gastrointestinal microflora and directly with the immune system. The possible health effects of probiotics include modulating the immune system and exerting antibacterial, anticancer, and anti-mutagenic effects. The purpose of this study was to isolate, identify, and characterize novel strains of probiotics from the faeces of Korean infants. Various assays were conducted to determine the physiological features of candidate probiotic isolates, including Gram staining, 16S rRNA gene sequencing, tolerance assays to stimulated gastric juice and bile salts, adherence ability assays, antibiotic susceptibility testing, and assays of immunomodulatory effects. Based on these morphological and biochemical characteristics, five potential probiotic isolates (Enterococcus faecalis BioE EF71, Lactobacillus fermentum BioE LF11, Lactobacillus plantarum BioE LPL59, Lactobacillus paracasei BioE LP08, and Streptococcus thermophilus BioE ST107) were selected. E. faecalis BioE EF71 and L. plantarum BioE LPL59 showed high tolerance to stimulated gastric juice and bile salts, and S. thermophilus BioE ST107 as well as these two strains exhibited stronger adherence ability than reference strain Lactobacillus rhamnosus GG. All five strains inhibited secretion of lipopolysaccharide-induced pro-inflammatory cytokines IL-6 and TNF-α in RAW264.7 macrophages in vitro. L. fermentum BioE LF11, L. plantarum BioE LPL59, and S. thermophilus BioE ST107 enhanced the production of anti-inflammatory cytokine IL-10. Overall, our findings demonstrate that the five novel strains have potential as safe probiotics and encouraged varying degrees of immunomodulatory effects.